MicroRNAs (miRNAs) in Neurodegenerative Diseases - Nelson, Peter T. (Blackwell Publishing Ltd, 2008)
Aging‐related neurodegenerative diseases (NDs) are the culmination of many different genetic and environmental influences. Prior studies have shown that RNAs are pathologically altered during the inexorable course of some NDs. Recent evidence suggests that microRNAs (miRNAs) may be a contributing factor in neurodegeneration. miRNAs are brain‐enriched, small (∼22 nucleotides) non‐coding RNAs that participate in mRNA translational regulation. Although discovered in the framework of worm development, miRNAs are now appreciated to play a dynamic role in many mammalian brain‐related biochemical pathways, including neuroplasticity and stress responses. Research about miRNAs in the context of neurodegeneration is accumulating rapidly, and the goal of this review is to provide perspective for these new data that may be helpful to specialists in either field. An overview is provided about the normal functions for miRNAs, including some of the newer concepts related to the human brain. Recently published studies pertaining to the roles of miRNAs in NDs––including Alzheimer's disease, Parkinson's disease and triplet repeat disorders—are described. Finally, a discussion is included with theoretical syntheses and possible future directions in exploring the nexus between miRNA and ND research.